Fumonisin B1 induces global DNA hypermethylation in human glioblastoma U87MG cells - Ashmika Foolchand; Terisha Ghazi; Anil A. Chuturgoon (Epigenetics)
Fumonisin B1 (FB1) is a common maize contaminant known to induce toxicity and carcinogenesis in humans and animals; however, its epigenetic mechanisms remain poorly understood. DNA methylation is an epigenetic modification that controls gene expression through DNA methyltransferase and demethylase activities. In this study, the effect of FB1 on DNA methylation in brain glioblastoma U87MG cells was evaluated. FB1 cytotoxicity was determined by the MTT assay and an IC50 value of 880 µM FB1 was obtained. The ELISA-based global DNA methylation assay displayed an increase in 5-methylcytosine levels. qPCR and western blot revealed a significant increase in DNA methyltransferase expressions (DNMT1, DNMT3A, and DNMT3B) and a significant decrease in demethylase expression (MBD2). This data indicates that FB1 induces global DNA hypermethylation, through increased DNA methyltransferase expressions and DNA demethylase suppression in U87MG cells, thus suggesting an alternative mechanism of toxicity.